2017
DOI: 10.15625/2525-2321.2017-00482
|View full text |Cite
|
Sign up to set email alerts
|

Lignans isolated from the ethyl acetate extract of Knema pachycarpa fruit

Abstract: Knema is a genus of tropical evergreen trees of the family Myristicaceae found in South East Asian countries such as Vietnam, Thailand, and Malaysia. In this paper, four lignans, (+)-pinoresinol (1),(+) epi-pinoresinol (2), piperitol (3), and pluviatilol (4), were isolated from the ethyl acetate extract of the fruit of Knema pachycarpa, an indigenus tree in Vietnam. The chemical structures were determined by spectroscopic data and comparison with the reported literature. These compounds were isolated from Knem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12] Knema plant exhibited antibacterial, anti-inflammatory, antioxidant, cytotoxic, and acetylcholinesterase inhibitory activities. [5][6][7][8][9][10][11][12][13][14] Several lignans have been reported from the ethyl acetate extract of K. pachycarpa fruits 15 but the chemical composition of the stems of this plant has not yet been investigated. Herein, we describe the isolation and structure elucidation of 2 new acetophenone derivatives named knepachycarpanone A (1) and knepachycarpanone B (2), together with a new cardanol derivative named knepachycarpanol C (3) from the ethyl acetate extract of the stems of K. pachycarpa.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Knema plant exhibited antibacterial, anti-inflammatory, antioxidant, cytotoxic, and acetylcholinesterase inhibitory activities. [5][6][7][8][9][10][11][12][13][14] Several lignans have been reported from the ethyl acetate extract of K. pachycarpa fruits 15 but the chemical composition of the stems of this plant has not yet been investigated. Herein, we describe the isolation and structure elucidation of 2 new acetophenone derivatives named knepachycarpanone A (1) and knepachycarpanone B (2), together with a new cardanol derivative named knepachycarpanol C (3) from the ethyl acetate extract of the stems of K. pachycarpa.…”
mentioning
confidence: 99%
“…The remaining compound 4 was identified as pinoresinol based on our spectroscopic data and by comparison with those of reported data given in CDCl 3 [15]. This compound is widely distributed throughout the plants in Viet Nam, e.g, Silybum marianum [16], Mallotus macrostachyus [17], Rhizophora stylosa [18], Trichosanthes kirilowii [19], Knema pachycarpa [20], and Balanophora laxiflora [21].…”
Section: Resultsmentioning
confidence: 80%
“…Plant Knema pachycarpa de Wilde, that is called "Mau cho trai day", is a native tree in Viet Nam and only few chemical studies of this Knema species have been reported by our group [5][6][7]. In our biological activity screening of Vietnamese plants, the MeOH extract of leaves of K. pachycarpa showed cytotoxic activity against KB cell line with IC 50 of 78.21 ± 4.35 g/mL.…”
Section: Introductionmentioning
confidence: 84%
“…In the continuation of our study on Knema plants, herein the chemical constituents of K. pachycarpa leaves were described. Seven phenolic compounds were isolated and elucidated as 5,7,3′-trihydroxy-5′-methoxy isoflavone (1), luteolin (2),(-)-narigenin (3), (+)-catechin (4), isoquercetrin (5), nicotiflorine (6), and 3,3',4,4'-tetrahydroxybiphenyl (7) by NMR and MS spectral data. The isolated compounds were evaluated for cytotoxicity against several cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%